2018
DOI: 10.5751/es-10344-230315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fisheries management on local ecological knowledge

Abstract: ABSTRACT. Local ecological knowledge, or the collective perceptions held by a particular group about their environment, results from the transmission of cultural knowledge from one generation to the next, combined with regular and persistent interactions between individuals and the biophysical environment. Management systems that limit access to certain natural resources likely have an effect on the quality of that knowledge. We explore the distribution of local ecological knowledge as it corresponds to differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 30 publications
1
20
0
1
Order By: Relevance
“…Resource users' perceptions of and interactions within marine social-ecological systems are impacted not only by external shocks and stressors, but also dynamic knowledge structures specific to the cultures of which they are a part ( Figure 5). Though cultural models are likely influenced by diverse factors whose relative importance may vary across study systems, our findings support the assertion that that livelihood practices (i.e., diversification) and assets (i.e., gear and permit ownership) are critical factors within SSF (Crona, 2006;Farr et al, 2018).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Resource users' perceptions of and interactions within marine social-ecological systems are impacted not only by external shocks and stressors, but also dynamic knowledge structures specific to the cultures of which they are a part ( Figure 5). Though cultural models are likely influenced by diverse factors whose relative importance may vary across study systems, our findings support the assertion that that livelihood practices (i.e., diversification) and assets (i.e., gear and permit ownership) are critical factors within SSF (Crona, 2006;Farr et al, 2018).…”
Section: Discussionsupporting
confidence: 76%
“…With a holistic emphasis on relationships, processes, and feedbacks (Walsh et al, 2013), LEK can reveal important information about changes to the structure and function of marine social-ecological systems and plays a critical role in defining how such changes are interpreted and understood as risk (Adger et al, 2009;Aswani et al, 2015). While western (i.e., scientific) knowledge is invaluable in quantifying trends and assessing taxonomic relationships (Moller et al, 2004), LEK can ground such findings in the context of specific places, actors, and harvesting dynamics (Farr et al, 2018), and can be used to describe emergent phenomena in real time (Johannes et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, in spite of overlaps, these two categories are separately discussed in this paper. Farr et al (2018) showed that fishery management regimes influence the content and expression of LEK. Continuing conflicts over access and gear use, and the long experience of discrimination, violence, poverty and social-economic marginality dominated the perceptions of fisher respondents (Choudhary et al, 2015;Kelkar, 2018;Kelkar & Krishnaswamy, 2014).…”
Section: Historical Experiences Of Fishery Conflicts and Lekmentioning
confidence: 99%
“…Local ecological knowledge refers to experiential, adaptive, practice-based learning and accumulation of relevant knowledge by people who depend strongly on ecosystems (Berkes, Colding, & Folke, 2000;Fazey, Fazey, Salisbury, Lindenmayer, & Dovers, 2006;Santha, 2008;Lertzman, 2010;Davis & Ruddle, 2010). The continuity of local ecological knowledge systems depends on the institutional capacities of fishing communities to access and manage fisheries (Butler, 2005;Farr, Stoll, & Beitl, 2018;Wilson et al, 2006).…”
mentioning
confidence: 99%